Distribution of Contact Pressures between the Pivoting Support and Tracks for Super Cranes - Guo, J.T.; Li, S.F.; Feng, L. (Проблемы прочности, 2015)
The pivoting support is a core structure that assures rotation of super full-rotation cranes. The surface-surface sliding-friction pivoting support is a new potentiality, yet several technical problems still need to be solved, e.g., equilibrium between the pivoting support and tracks. The distribution of contact pressures of three pivoting support models for four typical load cases was calculated. Analysis of contact pressures was based on the finite element method, and the distribution curves for circumferential contact pressures were plotted. The pivoting support design effect on the contact pressures is studied, demonstrating an optimum structure that provides for the contact pressures to be well distributed. Поворотная опора ключевая конструкция, обеспечивающая вращение полноповоротного крана сверхвысокой производительности. Конструкция поворотной опоры на контактных салазках трения скольжения открывает новые возможности, однако целый ряд технических проблем все еще нуждается в решении, в том числе равновесие между поворотной опорой и подкрановыми путями. Выполнен расчет распределения контактных давлений для трех моделей поворотной опоры и четырех типичных случаев нагружения. Анализ контактных давлений основан на методе конечных элементов, построены кривые распределения окружных контактных давлений. Изучено влияние конструкции поворотной опоры на контактные давления, предложена оптимальная конструкция, обеспечивающая равномерное распределение контактных давлений.